The Influence of Customer Interaction on Participation in Value Co-Creation: Evidence from Virtual Communities in China - Huang, Yue; Suo, Lu (Technium Social Sciences Journal, 2021)
This study aims to investigate the influence of customer interaction on customer participation in value co-creation. Quantitative approach is employed to gather data via online questionnaires from 502 Chinese registered members of various virtual brand communities, including Huawei Pollen Club, Xiaomi Community, Meizu Community and OnePlus Community. SEM is employed to analyze data of the research model. The results confirm that customer’s product engagement positively affect customer experience value including functional experience value, emotional experience value and social experience value three dimensions while interpersonal interaction significantly positive influence only emotional experience value and social experience value. Besides, emotional experience value and social experience value were found to have a significant positive effect on customer participation in value co-creation. Furthermore, our results determine that experience value plays a mediating effect in the influence of customer interaction on participating value co-creation. The findings fill in the gaps of previous relevant studies and enriches the research on the factors that drive customer participation in value co-creation. It also provides managerial insights for virtual communities to improve their service about customer participation and bring more business value.